CLINICAL AND MORPHOLOGICAL ASPECTS OF THE APPLICATION OF PLATELET GROWTH FACTORS IN PATIENTS WITH PILONIDAL CYST WITH ABSCESS - E. E. Achkasov; A. Ya. Solomka; A. A. Ulyanov; Е. N. Bezuglov; E. V. Orekhova; T. M. Zharikova (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The objective of this study is to investigate the surgical management of pilonidal cyst with abscess and to improve short-term and long-term outcomes.MATERIAL AND METHODS. The initial sample consisted of 353 patients operated for pilonidal cyst with abscess. The first group included 105 patients, receiving treatment with the excision of pilonidal cyst and the suturing in staggered rows. The second group consisted of 136 patients with the excision of pilonidal cyst using a unique patented technique. The third group of 112 patients underwent an identical operation to that of the second group, but with additional platelet growth factors (PGF) to improve the wound healing.RESULTS. The current study found that in comparison to the traditional technique, the optimal surgical treatment of pilonidal cyst with abscess was the original one-staged surgical technique, based on an economical excision, which led to an improvement in sickness leave of up to 27 days and in long-term outcomes (2 % of long-term complications). Another important finding was that the application of platelet growth factors (PGF) in the complex treatment of patients with pilonidal cyst with abscesses reduces the recovery time by up to 21 days and resulted in 30 % lower postoperative pain scores (Visual Analog Scale for Pain).CONCLUSION. In general, this finding shows that the original one-stage excision of pilonidal cyst with abscess with the application of PGF and with no suturing reduces disability time without increasing the number of early or late postoperative complications.